The Impact of Sport on the Health Related Quality of Life of Primary School Children - Halasi, Szabolcs; Lepes, Josip (Central European Journal of Educational Research, 2022)
By participating in some organized physical activities, even at school or in a sports association, children will have an impact on their intellectual, emotional and socialization abilities, as well as develop their motor skills and abilities. As a result, an athlete’s health will also be at a higher level and their Healthrelated quality of life (HRQOL) will change. In the survey, we were researching if there is a difference in the results of the HRQOL dimensions of lower-grade athletes and non-athletes at Ferenc Gál University’s Szarvasi Training Primary School and Training Kindergarten. In the cross-sectional study, 89 parents responded to questions in the Kidscreen-27 / proxy questionnaire, which asked about their child’s subjective quality of life and its relationship with sports. Based on the statistically processed data, it can be shown that young athletes have higher HRQOL values compared to their non-athlete counterparts in all dimensions. From this, we can conclude that sport has a positive impact on the health and well-being of athlete students, their relationships with family and friends, and their effectiveness at school.